Serum Lipase Amylase Ratio in Predicting Aetiology, Severity and Outcome of Acute Pancreatitis in a Tertiary Care Hospital - Haque, Majharul; Azam, Golam; Sarkar, Debashis Kumar; Rahman, Anisur (Bangladesh Critical Care Journal, 2017)
Background: Acute pancreatitis is a relatively common disease with variable prevalence in different countries. Different modalities are available for predicting aetiology, severity and outcome of acute pancreatitis with different sensitivity and specificity. Moreover, some are not widely available, some are very expensive. A single, cheap, widely available marker with high sensitivity and specificity is yet to be identified. The present study intends to find out the utility of serum lipase amylase ratio in predicting the aetiology, severity and outcome of acute pancreatitis. Methods: This prospective, observational study was done at the Department of Gastrointestinal Hepatobiliary & Pancreatic Disorders (GHPD), BIRDEM General Hospital, Dhaka, during the period of July 2014 to March 2016. A total of 71 patients with acute pancreatitis were included. Complete blood count, serum amylase, serum lipase, serum calcium, liver function test, renal function test, fasting lipid profile, ultrasonography of whole abdomen, CT scan of upper abdomen and arterial blood gas (ABG) were done in all patients. Statistical analysis was done with SPSS version 16. Results: Among 71 patients, 23(32.4%) were due to biliary cause, 15(21.1%) were due to hypertriglyceridaemia, 4(5.6%) were due to alcohol and 22(31%) were due to unknown causes. 45 (63.4%) patients had mild attack, 10(14.1%) patients had moderate attack and 16(22.5%) patients had severe attack of acute pancreatitis. Out of 71 patients, 17(23.9%) developed complication whereas 54(76.1%) developed no complication. Serum lipase amylase ratio in patients with biliary pancreatitis was 1.40±0.39 and in patients with non-biliary pancreatitis was 2.39±0.84(p <0.001). Again, serum lipase amylase ratio in patients with acute alcoholic pancreatitis was 2.89±0.79 and in patients with non-alcoholic acute pancreatitis was 1.95±0.81 (p=0.002). Serum lipase amylase ratio in patients with acute pancreatitis due to hypertriglyceridaemia was 2.75±0.68 and in patients with acute pancreatitis due to other than hypertriglyceridaemia was 1.62±.65(p< 0.001). This study showed that serum lipase amylase ratio was <2.0 in acute biliary pancreatitis and this ratio was >2.5 in acute alcoholic pancreatitis and in acute pancreatitis due to hypertriglyceridaemia. Serum lipase amylase ratio in patients with mild acute pancreatitis was 1.95±0.89; in patients with moderately severe acute pancreatitis the ratio was 2.37±0.92 and in patients with severe acute pancreatitis, the ratio was 2.22±0.70. The difference of lipase amylase ratio among these groups of patients was not statistically significant (p=0.273). Mean lipase amylase ratio among the patients without complication of acute pancreatitis was 2.03±0.92 whereas this ratio among the patients with complication was 2.17±0.68. This difference of lipase amylase ratio was not statistically significant (p=0.557). Conclusion: Role of serum lipase amylase ratio in predicting the aetiology and severity of acute pancreatitis has been addressed in several recent studies. This study was another attempt to achieve this goal. Predicting the aetiology of acute pancreatitis by such a cheap tool will guide further diagnostic work up and management strategy will avoid unnecessary investigations. Bangladesh Crit Care J September 2017; 5(2): 88-92